2020
DOI: 10.1101/2020.10.27.20220863
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Retrospectivein silicoHLA predictions from COVID-19 patients reveal alleles associated with disease prognosis

Abstract: Background: The Human Leukocyte Antigen (HLA) gene locus plays a fundamental role in human immunity, and it is established that certain HLA alleles are disease determinants. Methods: By combining the predictive power of multiple in silico HLA predictors, we have previously identified prevalent HLA class I and class II alleles, including DPA1*02:02, in two small cohorts at the COVID-19 pandemic onset. Since then, newer and larger patient cohorts with controls and associated demographic and clinical data have b… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 40 publications
3
39
1
Order By: Relevance
“…Also, after correcting for multiple testing, we did not find significant associations of single allotypes with COVID-19 severity. These results suggest that individual HLA genotypes do not limit the immune response to SARS-CoV-2 infection as presumed by other studies ( 14 16 , 36 ). Clinical factors such as age and body mass index had a far greater impact in our population compared to any analyzed factor describing the individual set of HLA molecules ( 34 ).…”
Section: Discussionsupporting
confidence: 71%
“…Also, after correcting for multiple testing, we did not find significant associations of single allotypes with COVID-19 severity. These results suggest that individual HLA genotypes do not limit the immune response to SARS-CoV-2 infection as presumed by other studies ( 14 16 , 36 ). Clinical factors such as age and body mass index had a far greater impact in our population compared to any analyzed factor describing the individual set of HLA molecules ( 34 ).…”
Section: Discussionsupporting
confidence: 71%
“…On the contrary, we found that only one out of eight HLA-A*02:01 or HLA-A*03:01 homozygous individuals died before 60 years. This fact can be also observed in dataset recently published by Warren with co-authors [35]: none out of five COVID-19 patients homozygous by HLA-A*02:01 or HLA-A*03:01 had severe course of COVID-19 and were admitted to intensive care unit. Thus, presentation of “important” viral peptides with doubled intensity can enhance immune response showing that HLA class I homozygosity can act like a double-edged sword.…”
Section: Discussionsupporting
confidence: 64%
“…In a preprint article, HLA-A*30:02 was found to be enriched among COVID-19 patients compared with controls without COVID-19, although the association was not statistical significant after adjusting for multiple comparisons. 35 The study appeared to be underpowered with 100 COVID-19 patients and 26 controls, and the descent or ethnicity of the study population was not reported. Our finding of HLA-A*30:02 as a risk factor for COVID-19 among younger African Americans is consistent this earlier report and needs to be confirmed by further studies.…”
Section: Discussionmentioning
confidence: 99%